Green consumer buying behaviour: antecedents, selection attributes of generation Y consumers and the relationship with future behavioural intentions - Muposhi, Asphat (My University, 2015)
The concept of green marketing has gained prominence in academia in recent years with concomitant implications for marketing strategy. The considerable attention accorded to green marketing is accentuated by concerns about global climate change and its threat to the sustainability of livelihoods. As the debate on green marketing continues to unfold, there are important issues yet to be addressed, one of which relates to the antecedents of green consumer buyer behaviour and selection attributes of green products. In view of the growing importance of green consumer buyer behaviour in contemporary markets, the purpose of the present study was to examine empirically the antecedents of green consumer buyer behaviour and the selection attributes of Generation Y consumers. The Generation Y cohort was considered as the ideal target population for the present study owing to its size, bespeaking a profitable market segment with the potential to provide a “snap-shot” of future pro-environmental behavioural intentions. The theories of Reasoned Action and Consumption Values provided the theoretical lens through which to examine and delineate the antecedents of green consumer buyer behaviour and the selection attributes of Generation Y consumers in the context of a developing country such as South Africa. The present study adopted a sequential mixed-methods methodology that commenced with a qualitative study and was followed by a quantitative study. For the qualitative study, data were collected from a purposively selected Generation Y student sample comprising sixteen participants. The principle of technical saturation was employed to ascertain the adequacy of the sample size. The credibility and trustworthiness of the qualitative study were achieved through pretesting of the interview guide, bracketing, prolonged ngagement with participants, member checks, peer de-briefing, an audit trail of the interviewing process and researcher reflexivity. The analysis of the qualitative data was conducted through the use of content and thematic analyses. The qualitative study identified environmental attitude, environmental concern, social influence, environmental responsibility, government influence, selection attributes and green purchase intention as the main determinants of green purchase behaviour. The qualitative study also revealed that the demand for green products is thwarted by marketing-related barriers such as high prices, misleading green marketing messages and unavailability of products. In line with the methodology of the study, the determinants of green purchase behaviour that emerged from the qualitative study were further examined through a quantitative study. The data for the quantitative study were generated from a conveniently selected Generation Y student sample of 386 respondents, using a structured selfadministered questionnaire. The historical evidence method and the pre-conditions of multivariate data analysis (confirmatory factor analysis) guided the determination of the sample size for the quantitative study. The statistical data analysis procedures utilised for the quantitative study were descriptive statistics, reliability and validity analysis, correlation analysis, confirmatory factor analysis and structural equation modelling. Prior to questionnaire administration, a pilot study was conducted to improve the accuracy of the survey instrument. The collected quantitative data were analysed using the Statistical Package for the Social Sciences (SPSS) 22.0 and Analysis of Moment Structures (AMOS) 22.0. The preliminary data analysis involved the process of coding and checking the distribution of scores. The results of the normality test revealed that the data were not normally distributed. Thus, non-parametric statistics were employed for correlation analysis and for testing gender difference in green consumer buyer behaviour. The Mann-Whitney U Test and the Kruskal-Wallis Test revealed that Generation Y female consumers are more apt to engage in pro-environmental behaviours than their male counterpartsIn order to verify the reliability of the measurement items, Cronbach’s alpha coefficient, the item-to-total values and composite reliability were computed. In addition, the validity of the survey instrument was enhanced through content, convergent, discriminant and predictive validities. The reliability and validity measures employed in the present study attested that the survey instrument utilised in the quantitative study was both reliable and valid. The results of correlation analysis indicated that environmental concern, environmental attitude, environmental responsibility, government influence, social influence and selection attributes have a positive association with green purchase intention. The correlation analysis also revealed a weak association between green purchase intention and actual purchase behaviour. Prior to testing the hypothesised relationships, the fitness of the measurement and structural models was assessed. The model fit indices that included the chi-square value over degree of freedom ( 2/df), Goodness-of-Fit Index (GFI), Root Mean Square Error of Approximation (RMSEA), Comparative Fit Index (CFI), Incremental Fit Index (IFI) andTucker-Lewis Index (TLI) yielded satisfactory results that are consistent with acceptable thresholds, demonstrating that the measurement and structural model fitted well with the data. The posited relationships were tested using structural equation modelling. The hypotheses testing results revealed that green purchase intention was significantly and positively influenced by environmental attitude, environmental concern, social influence, environmental responsibility and selection attributes, but not by government influence. The results also showed that the relationship between green purchase intention and actual purchase behaviour was moderated by selection attributes. The findings of the study imply that marketers need to formulate and implement green marketing strategies that enhance environmental attitudes and concerns, initiate programmes that foster environmental responsibility, understand the selection attributes of Generation Y consumers and utilise social networks to stimulate pro-environmental behaviours. The results also suggest that the South African government needs to re-invigorate its environmental initiatives to foster green purchase intention and the purchase of green products. Finally, the study also provided evidence that suggests an insignificant relationship between green purchase intention and actual purchase behaviour. This result suggests an urgent need by marketers to understand the underlying factors causing the gap between green purchase intention and actual purchase behaviour. To effectively promote green consumer buyer behaviour, marketers need to understand the determinants of green purchase intention and craft effective strategies to translate green purchase intentions into actual purchasing behaviour. The findings of the present study provide avenues for further study in a discipline that is increasingly gaining theoretical and practical prominence. Future research efforts should consider the use of an integrated research model that encompasses more variables, utilising a broader sample frame and employing a longitudinal study in order to enhance the generalisability of the research findings. Overall, the study offers valuable insights for stimulating green purchase behaviour among the potentially profitable Generation Y cohort and equips marketers with green marketing strategies to position green products competitively in the marketplace.
D. Tech. (Marketing, Department of Marketing and Sport Management, Faculty of Management Sciences) Vaal University of Technology
Keywords: Green marketing; Marketing strategy; Green consumer behaviour; Generation Y consumers; Pro-environmental intentions; Purchase behaviour; 658.802; Green marketing